Monitoring the agri-food system in Myanmar: The rising costs of diets and declining purchasing power of casual wage laborers: December 2021–June 2024 - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
We assess changes in food prices and purchasing power of casual wage laborers based on large-scale surveys of households and food vendors (fielded from December 2021 until June 2024) in rural and urban areas and in all states/regions of Myanmar.